The Extra Virgin Olive Oil Polyphenol Oleocanthal Exerts Antifibrotic Effects in the Liver - Gabbia, Daniela; Carpi, Sara; Sarcognato, Samantha; Cannella, Luana; Colognesi, Martina; Scaffidi, Michela; Polini, Beatrice; Digiacomo, Maria; Esposito Salsano, Jasmine; Manera, Clementina; Macchia, Marco; Nieri, Paola; et al. (Frontiers in Nutrition, 2021)
Liver fibrosis, which is the outcome of wound-healing response to chronic liver damage, represents an unmet clinical need. This study evaluated the anti-fibrotic and anti-inflammatory effects of the polyphenol oleocanthal (OC) extracted from extra virgin olive oil (EVOO) by an in vitro/in vivo approach. The hepatic cell lines LX2 and HepG2 were used as in vitro models. The mRNA expression of pro-fibrogenic markers, namely alpha-smooth muscle actin (α-SMA), collagen type I alpha 1 chain (COL1A1), a panel of metalloproteinases (MMP1, MMP2, MMP3, MMP7, MMP9) and vascular endothelial growth factor A (VEGFA) as well as the pro-oxidant genes NADPH oxidases (NOXs) 1 and 4 were evaluated in TGF-β activated LX2 cells by qRT-PCR. α-SMA and COL1A1 protein expression was assessed by immunofluorescence coupled to confocal microscopy. VEGFA release from LX2 was measured by ELISA. We also evaluated the amount of reactive oxygen species (ROS) produced by H2O2 activated- HepG2 cells. In vivo, OC was administered daily by oral gavage to Balb/C mice with CCl4-induced liver fibrosis. In this model, we measured the mRNA hepatic expression of the three pro-inflammatory interleukins (IL) IL6, IL17, IL23, chemokines such as C-C Motif Chemokine Ligand 2 (CCL2) and C-X-C Motif Chemokine Ligand 12 (CXCL12), and selected miRNAs (miR-181-5p, miR-221-3p, miR-29b-3p and miR-101b-3p) by qRT-PCR. We demonstrated that OC significantly downregulated the gene/protein expression of α-SMA, COL1A1, MMP2, MMP3, MMP7 and VEGF as well as the oxidative enzymes NOX1 and 4 in TGFβ1-activated LX2 cells, and reduced the production of ROS by HepG2. In vivo OC, beside causing a significant reduction of fibrosis at histological assessment, counteracted the CCl4-induced upregulation of pro-fibrotic and inflammatory genes. Moreover, OC upregulated the anti-fibrotic miRNAs (miR-29b-3p and miR-101b-3p) reduced in fibrotic mice, while downregulated the pro-fibrotic miRNAs (miR-221-3p and miR-181-5p), which were dramatically upregulated in fibrotic mice. In conclusion, OC exerts a promising antifibrotic effect via a combined reduction of oxidative stress and inflammation involving putative miRNAs, which in turn reduces hepatic stellate cells activation and liver fibrosis.